The data acquisition and calibration system for the ATLAS semiconductor tracker - Abdesselam, A; Barber, T; Barr, A; Bell, P; Bernabeu, J; Butterworth, J; Carter, JR; Carter, A; Charles, E; Clark, A; Colijn, A; Costa, M; et al. (2008)
The SemiConductor Tracker (SCT) data acquisition (DAQ) system will calibrate, configure, and control the approximately six million front-end channels of the ATLAS silicon strip detector. It will provide a synchronized bunch-crossing clock to the front-end modules, communicate first-level triggers to the front-end chips, and transfer information about hit strips to the ATLAS high-level trigger system. The system has been used extensively for calibration and quality assurance during SCT barrel and endcap assembly and for performance confirmation tests after transport of the barrels and endcaps to CERN. Operating in data-taking mode, the DAQ has recorded nearly twenty million synchronously-triggered events during commissioning tests including almost a million cosmic ray triggered events. In this paper we describe the components of the data acquisition system, discuss its operation in calibration and data-taking modes and present some detector performance results from these tests. © 2007 IOP Publishing Ltd and SISSA.